PENYUSUNAN LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) CV. KAYRA COMPUTER BATAM - Futry Rezeqy; Lukman Hakim Siregar (Worksheet : Jurnal Akuntansi, 2022)
The formulation of the problem in this study is how to prepare financial statements based on financial accounting standards for entities without public accountability (SAK ETAP) on Cv. Kayra Computer Batam?, and how is the process of preparing financial reports on Cv. Kayra Computer Batam?. The purpose of this study was to determine the preparation of financial statements based on financial accounting standards for entities without public accountability (SAK ETAP) on Cv. Kayra Computer Batam, and to know the process of preparing financial statements, on Cv. Kayra Computer Batam. This research was conducted at Cv. Kayra Computer Batam. This type of research is descriptive research. The data analysis used in this research is qualitative analysis.